PERTUMBUHAN BIBIT KARET (Hevea brasiliensis) DENGAN PEMBERIAN GIBERELINE BERBAGAI KONSENTRASI DAN PUPUK KANDANG AYAM BERBAGAI DOSIS - Krisnarini Krisnarini; Yatmin Yatmin (Jurnal WACANA PERTANIAN, 2014)
The growth of caoutchouc seed by applying gibereline hormone in various concentrations and chicken manure in various dosages (Krisnarini). The application of ZPT gibereline in various dosages gives the same influence in the growth of caoutchouc seed which is supported by all the observation variables, the mixture comparison of chicken manure: soil (2:1) gives the tallest result of caoutchouc seed’s growth which is supported by the height of caoutchouc seed, root volume, dried shoot mass and dried root mass variables.Keywords: Caoutchouc seed, Gibereline and chicken manur